Interdisciplinary measures : literature and the future of postcolonial studies - Huggan, Graham, 1958- (Postcolonialism across the disciplines, 2008)
Where now for postcolonial studies? That is the central question in this new volume from one of the field?s most original thinkers. Huggan's answer is interdisciplinarity and here he sets out a series of conversations between literary studies and other disciplines, notably geography, environmental studies, history and anthropology. Huggan aims to establish an alternative trajectory through the field of postcolonial literary/cultural studies that is alert to similar kinds of work being done in and across other disciplines; and reflects on possible futures for postcolonial studies that move beyond.